THE IMPACT OF WORKPLACE SPRITUALITY AND TRANSFORMATIONAL LEADERSHIP MEDIATED BY JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Adam Maulana; Justine Tanuwijaya; Viraditya Nadine Al Faritsi; Dinda Fitri Andari; Norzanah Mat Nor (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The purpose of this research is to identify and analyze the influence of workplace spirituality and transformational leadership, mediated by job satisfaction, on the organizational citizenship behavior of employees at PT. Chandra Asri Petrochemical and PT Asahimas Chemical. All respondents in this study are employees of PT. Chandra Asri Petrochemical and PT Asahimas Chemical. Data collection methods were conducted through the distribution of questionnaires to 308 employees of PT. Chandra Asri Petrochemical and PT. Asahimas Chemical uses the purposive sampling technique for sample selection. Hypothesis testing was conducted using the structural equation model (SEM) method. The results of this study indicate that workplace spirituality has a positive influence on organizational citizenship behavior, workplace spirituality has a positive effect on job satisfaction, transformational leadership has a positive effect on organizational citizenship behavior, transformational leadership does not have a positive effect on job satisfaction, job satisfaction has a positive effect on organizational citizenship behavior, workplace spirituality has a positive effect on organizational citizenship behavior mediated by job satisfaction, and transformational leadership does not have a positive effect on organizational citizenship behavior mediated by job satisfaction. The managerial implications of this research require the company to enhance patience among coworkers, pay more attention to individual support for staff, increase the enjoyment aspect of work, and give more attention to employees who are reluctant to use their time for voluntary work. Keywords: Workplace Spirituality; Transformational Leadership; Job Satisfaction; Organizational Citizenship Behavior